Melting Process Investigation of KCl Salt as a PCM by Enthalpy-Porosity Simulation Model with Temperature-dependent Physical Properties - Hasan, Muhammad Miqdad; Luthfie, Alief Avicenna (MSD Institute, 2024)
Salt as a phase change material (PCM) in thermal energy storage (TES) can store solar thermal energy in the form of latent heat by experiencing a process known as the melting process. Recently, the melting process can be observed and investigated using an enthalpy-porosity simulation model. However, the use of enthalpy-porosity simulation model is still focused on constant physical properties, i.e., density and viscosity, of the PCM, and thus, the changes in the physical properties with respect to temperature during the melting process are not included in the simulation process. Therefore, this study aims to use the enthalpy-porosity simulation model with temperature-dependent physical properties of the PCM to investigate the melting process. The salt in this study is Potassium Chloride (KCl), and the computational domain is a concentric tube based on the assumption that the salt is fully contained within the computational domain. The physical properties of the KCl salt (density and viscosity) are set as functions of temperature to include the changes in the physical properties with respect to temperature during the melting process. The simulation results show that the melting process period is 450 s. In addition, the tendency of the melting rate, which is defined as the change in liquid fraction per unit time, is observed to decrease during the melting process. Compared with the constant physical properties of the KCl salt, the melting period of the KCl salt with temperature-dependent physical properties is observed to be shorter, with a deviation of 28.57%.